Resource variation in colorectal surgery: a national centre level analysis. (July 2017) - Drake, T. M.; Lee, M. J.; Senapati, A.; Brown, S. R.
Abstract: Aim: Delivery of quality colorectal surgery requires adequate resources. We set out to assess the relationship between resources and outcomes in English colorectal units. Method: Data were extracted from the Association of Coloproctology of Great Britain and Ireland resource questionnaire to profile resources. This was correlated with Hospital Episode Statistics outcome data including 90‐day mortality and readmissions. Patient satisfaction measures were extracted from the Cancer Experience Patient Survey and compared at unit level. Centres were divided by workload into low, middle and top tertile. Results: Completed questionnaires were received from 75 centres in England. Service resources were similar between low and top tertiles in access to Confidential Enquiry into Patient Outcome and Death (CEPOD) theatre, level two or three beds per 250 000 population or the likelihood of having a dedicated colorectal ward. There was no difference in staffing levels per 250 000 unit of population. Each 10% increase in the proportion of cases attempted laparoscopically was associated with reduced 90‐day unplanned readmission (relative risk 0.94, 95% CI 0.91−0.97, P < 0.001). The presence of a dedicated colorectal ward (relative risk 0.85, 95% CI 0.73−0.99, P = 0.040) was also associated with a significant reduction in unplanned readmissions. There was no association between staffing or service factors and patient satisfaction. Conclusion: Resource levels do not vary based on unit of population. There is benefit associated with increased use of laparoscopy and a dedicated surgical ward. Alternative measures to assess the relationship between resources and outcome, such as failure to rescue, should be explored in UK practice.